CFD를 이용한 KRISO 추진효율 향상 장치(K-duct)의 성능 해석 - 서성부(Sung-Bu Suh) (Han-guk haeyang gonghak hoeji (Online), 2017)
This paper provides numerical results for the estimation of the efficiency of KRISO energy saving devices in the design stage. A finite volume method is used to solve Reynolds averaged Navier-Stokes (RANS) equations, where the SST k-$ω$ model is selected for turbulence closure. The propeller rotating motion is determined using a rigid body motion (RBM) scheme, which is called a sliding mesh technique. The numerical analysis focuses on predicting the power reduction by the designed KRISO devices (K-DUCT) under a self-propulsion condition. The present numerical results show good agreement with the available experimental data. Finally, it is concluded that CFD can be a useful method, along with model tests, for assessing the performance of energy saving devices for propulsion efficiency improvement.